An Introduction to Software Quality Assurance and its Implementation - Darrel Ince (Mcgraw Hill Book Company, 1994)
This book will show you how to build up an efficient, workable system from fundamental principles through to writing procedures and gaining ISO 9001 Certification. Preface, Software Tasks, Some Quality Assurance Questions, Project Planning, Requirements Analysis, System Design, Detailed Design and Programming, Testing, Configuration Management, Process Modelling, Standards and Procedures, ISO 9001, Case Study, Improving a Quality System, Bibliography, Index.